Konveksi Alam Dalam Medium Berpori = Natural Convection in Porous Media - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2002)
ABSTRACT Natural convection in porous media is a complex phenomenon. Consequently the govening equations related are also complicated and verry difficult to solve exatly. The objective of the research is to determine the influence of thermophysical properties of the porous media on the natural convection heat transfer. The reasearch investigated the effect of Rayleigh number on convection heat transfer in porous media filled water in a 50 cm length, 5 cm width and 50 cm heigh model heated isothermally from below. From four variations of the media Rayleigh number, 42.23, 165.81, 374.53 and 421.84, it is concluded that the higher in Rayleigh number the higher in convection heat transfer.